Fishers' Ecological Knowledge and Stable Isotope Analysis Reveal Mangrove Estuaries as Key Developmental Habitats for Critically Endangered Sea Turtles - Wedemeyer-Strombel, Kathryn R.; Seminoff, Jeffrey A.; Liles, Michael J.; Sánchez, Ramón Neftali; Chavarría, Sofía; Valle, Melissa; Altamirano, Eduardo; Gadea, Velkiss; Hernandez, Nicolas; Peterson, Markus J.; Smith, Kerri J.; Trueman, Clive N.; et al. (Frontiers in Conservation Science, 2021)
Successful conservation of endangered, migratory species requires an understanding of habitat use throughout life stages. When dedicated scientific studies are difficult to conduct, local expert knowledge can provide crucial baseline data to guide study design and aid data interpretation. In 2008, fishers in El Salvador demonstrated that eastern Pacific hawksbill sea turtles (Eretmochelys imbricata)—a population conservation biologists considered virtually extirpated—use mangrove estuaries as nesting habitat rather than open-coast beaches used by hawksbills in other regions. We confirmed and amplified this observation by using fishers' ecological knowledge to guide biological sampling for stable isotope analysis to assess if eastern Pacific hawskbills use mangrove-dominated estuaries as developmental habitats. We found that immature hawksbills experience a pelagic stage and then recruit to estuaries at ~37 cm curved carapace length, where they increase reliance on estuarine resources until they approach adult sizes. This life history strategy makes them especially vulnerable to in-water nearshore threats, and necessitates targeted expansion of conservation efforts throughout the eastern Pacific. Our analysis also provides a model for integrating traditional scientific approaches with local knowledge—a model that could yield crucial advances in other understudied regions.